Incidence and histomorphological characterization of canine neoplasms - Praveena Babu (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 2010)
The present study entitled “Incidence and histomorphological characterization of canine neoplasms” was conducted to assess the incidence of neoplasms among canines. Canine cases presented to the Veterinary hospitals of Mannuthy and Kokkalai and carcass brought for post mortem examination in the Centre of Excellence in Pathology, COVAS, Mannuthy from December 2008 to December 2009 was utilized for the study. Besides age, sex, breed and location wise incidence of tumours, haematological parameters, gross and histopathological features along with apoptotic index, mitotic index and AgNOR counts were recorded. A total of 61 tumour cases were recorded in 60 animals. Age, sex and breed wise analysis revealed that 55 percent of tumour bearing animals were in 5 to 8 year group, 58 percent of the affected animals were females while 42 percent were males and German shepherds, were the most affected - 28.33 percent. Among the cases studied benign tumours comprised 66 percent and malignant tumours were 34 percent. Moreover tumours of the skin and soft tissues constituted 32.8 percent, mammary tumours 29.51 percent and tumours of the genital system 21.31 percent. Tumours of the alimentary tract contributed 6.56 percent, 4.92 percent of tumours were from the haemolymphatic system, 3.3 percent tumours were of eye and ear origin and one tumour case (1.64 percent) from bone. Anaemia and leucocytosis are the haematological changes noticed in tumour bearing animals. The mean values of MI and AgNOR counts of benign and malignant tumours showed significant variation. Besides the MI and AgNOR counts were highly correlated. The tumours such as sebaceous gland tumours, eccrine carcinoma, melanocytoma, fibroma, neurofibroma, malignant fibrous histiocytoma, liposarcoma, hemangiosarcoma, osteosarcoma, lymphosarcoma, acute lymphoblastic leukemia, canine multicentric lymphoma, epulis, hepatic tumours, pancreatic carcinoma, adenoma of the nictitans gland, ceruminous carcinoma, sertoli cell tumor, TVT and mammary tumours were recorded.